Wpływ motywacji do nauki na ściąganie w szkole - Góźdź, Joanna (Studia Edukacyjne, 2020)
The article presents the problem of cheating in Polish schools. 1,070 students of high schools were examined. The aim of the research was to establish relationships between amotivation, external motivation, introjected motivation, motivation based on identification and internal one, and cheating, help to cheat and reluctance to help to cheat. The results show that amotivation, introjected and internal motivation are predictors of cheating. Only the external motivation turned out to be the predictor of help to cheat; on the basis of internal motivation it is possible to anticipate reluctance to help to cheat.